Stres No More: Strategi Efektif Mengelola Stres di Tengah Kehidupan Digital - Hendrikson Febri (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
In today's fast-paced and always-connected digital life, many individuals experience increased stress due to various reasons. Major issues in the digital era include constant connectivity, information overload, social media pressure, distractions and multitasking, work-life balance, social isolation, and mental and physical health concerns. The aim of this research is to explore how to manage stress effectively to achieve a state of